Analisis Petrografi dan Kualitas Batubara Sinjai, Sulawesi Selatan - Sufriadin Sufriadin; Sri Widodo; Yulinaus Mendaun (Jurnal Penelitian Enjiniring, 2018)
The investigation of coal deposits located in Sinjai Regency has been performed with the aim at elucidation of petrographic and quality of coal represented by ash and sulfur total content and its implication for the potential use of this coal. Field observation indicated the coal seams were relatively thin (<2m) and were associated with well-bedded, fine to medium grained tuffs. Petrografic analysis exhibited that vitrinite is dominant maceral group containing in coal followed by inertinite. Liptine is also present in small amount mainly sporinite and resinite. The mineral matter content was dominated by clay minerals and small quantity of pyrite. The Rv-max value of 0.40% indicates sub bituminous coal rank according to ASTM (1981) classification. Ash content of studied coal ranges from 8.8 to 40.2% indicating a medium to high ash coal whereas total sulfur shows the low concentration (<1%) implying the coal is classified as low sulfur. The elevated concentration of vitrinite in the sample studied indicate the suitability use for solid fuel combustion particularly in power plant and cement factory, whereas the low content of liptinite and inertinite are not favorable for liquifaction and coke making respectively.